Comparative Analysis of Oil Palm Production in Areas with and without Land Application of POME - Fachrul Egar; Syamuddin Harahap; Salwa Alya Putri Lubis; Parlindungan Gultom (Akademi Komunitas Perkebunan Yogyakarta, 2026)
The oil palm industry plays an important role in Indonesia’s economy. One of the key issues in plantation management is the utilization of Palm Oil Mill Effluent (POME). This study aims to analyze the differences in Fresh Fruit Bunch (FFB) production between land application and non-land application areas at PT Perkebunan Nusantara IV Regional III Sei Garo Estate. This study used a quantitative comparative method with a time series approach based on secondary data from 2022–2025. Variables observed included average bunch weight (kg/bunch), number of bunches (bunch/ha), and FFB production (ton/ha/semester). Data analysis included descriptive statistics, Shapiro–Wilk normality test, and Independent Sample t-test. The results showed that average FFB production in land application areas (10.29 ton/ha/semester) was slightly higher than non-application areas (10.06 ton/ha/semester). However, statistical tests indicated no significant differences in average bunch weight (p=0.945), number of bunches (p=0.068), and FFB production (p=0.881). It is concluded that POME application tends to increase production, although the effect is not statistically significant